Identification of alternatively spliced mRNAs encoding potential new regulatory proteins in cattle infected with bovine leukemia virus. - Alexandersen, S (1993)
The polymerase chain reaction was used to detect and characterize low-abundance bovine leukemia virus (BLV) mRNAs. In infected cattle we could detect spliced mRNA with a splice pattern consistent with a Tax/Rex mRNA, as well as at least four alternatively spliced RNAs. Two of the alternatively spliced mRNAs encoded hitherto unrecognized BLV proteins, designated RIII and GIV. The Tax/Rex and alternatively spliced mRNAs could be detected at their highest levels in BLV-infected cell cultures; the next highest levels were found in samples from calves experimentally infected at 6 weeks postinoculation. Alternatively spliced mRNAs were also expressed, albeit at lower levels, in naturally infected animals; they were detected by a nested polymerase chain reaction. Interestingly, the GIV mRNA was specifically detected in naturally infected cows with persistent lymphocytosis and in two of five calves at 6 months after experimental infection with BLV. Furthermore, the calf with the strongest signal for GIV had the highest lymphocyte counts. These data may suggest a correlation between expression of the GIV product and development of persistent lymphocytosis. Some of the donor and acceptor sites in the alternatively spliced mRNAs were highly unusual. The biological mechanisms and significance of such a choice of unexpected splice sites are currently unknown.